Screening and Characterization of L-Asparaginase Free L-Glutamianse Produced by Marine Bacterial Isolates - Larasati, Dinar Rahmi; Setiawan, Ruby; Wijarnaka, Wijarnaka; Pujiyanto, Sri (Berkala Bioteknologi, 2023)
L-asparaginase (EC 3.5.1.1) is a potential pharmaceutical enzyme for ALL (Acute Lymphoblastic Leukemia) treatment. However, it can cause side effects due to the activity of enzyme L-glutaminase. Halophilic microorganisms might be potential source of the enzyme L- asparaginase free of L-glutaminase because of these microorganism are adapted to extreme environments which producing biocatalysts with different structures. The enzyme was screened from marine bacterial isolated from surface sea water and marine sediment. The enzyme was produced and characterized for optimum temperature, pH, and the effect of metal ions. The results showed that a total of 96 marine bacterial isolates, three isolates namely Pseudomonas stutzeri, Marinobacter nitratireducens, Vibrio neocaledonicus were detected by producing L asparaginase free L-glutaminase. The highest activity was produced by Marinobacter nitratireducens, 0.887 U/ml. Enzyme production at the 60 hours showed the highest enzyme activity 1,625 U/ml and specific activity 1,700 U/mg. The maximum L-asparaginase activity occurs at temperature 40 °C and pH 8 of Tris HCl buffer. The relative activity of enzymes decreases due to the presence of metal ion K+ 5 mM, and Mg2 +, Ni2+, Cu2+, Zn2+ 1 mM and 5 mM.